A Presença das narrativas tradicionais no imaginário dos jovens da idade escolar - SALES, Maria da Luz Lima (2014)
This qualitative research aims the imaginary's study about fantastic characters from the myths and legends in Colares, in the state of Pará. Colares is a place that within its culture continues to habitually tell traditional stories. These stories merge indigenous and mythical elements of mestizo shammausism as well as other religious elements that are found within Brazilian story telling culture. These stories from Colares contain a subliminal moral message that is achieved by joining reality with fiction. They are narratives that contain residues of stories from ancient cultures, capturing individual and collective fears and translated from generation to generation through story telling. To analyse it, interviews were conducted with young almost final year high school students at a local public school, aged between sixteen and eighteen, in order to investigate the feelings and sensations triggered by reading or hearing the narrative, emphasizing fear and beliefs. Our research found that teenagers cherishes the traditional narratives and are inclined to believe in such figures as Boto, Matintaperera the and Cobra Grande contained in them, because the fear which is caused by these creatures; and that these narratives have the effect of emerging unconscious problems bringing them up awareness, working as a therapy that takes the reader or listener to the realization of his personality.